Acute onset psychosis with complex neurobehavioural symptomatology following the intramuscular injection of hyoscine butylbromide: A case report with an overview of the literature - (:unkn) unknown (BMJ Publishing Group, 2021)
Different compounds of hyoscine (scopolamine) are widely used for the treatment of a variety of conditions, ranging from motion sickness to colic spasms and smoking cessation. In some rare conditions, the administration of scopolamine may lead to severe idiosyncratic reactions, including central anticholinergic intoxication syndrome. Here, we present a young female patient who progressively developed a series of complex neuropsychiatric symptoms including ataxia, slurred and rambling speech, stereotypic movements, vivid visual and auditory hallucinations, and self-mutilative behaviours in the days following the injection of hyoscine butylbromide in the emergency room to treat her menstrual cramps. Referred to psychiatry, detailed screening of her medical records and collateral information from the family revealed that the neurobehavioural manifestations were indeed preceded by severe peripheral anticholinergic toxicity, which were mostly overlooked during the initial evaluations. Started on olanzapine treatment, the patient's symptoms gradually subsided over time, though it took several weeks to achieve full clinical recovery. © European Association of Hospital Pharmacists 2020. No commercial re-use. See rights and permissions. Published by BMJ.
Keywords: emergency medicine; neurology; psychiatry; self-injurious behavior; toxicology